The microbiome of The Egyptian Red Sea proper and Gulf of Aqaba - Mustafa, Ghada Alaa El-Din (AUC Knowledge Fountain, 2016)
The Red Sea is one of the most unique environments worldwide. It possesses a unique geography, physical, chemical and biological characteristics. It encounters several ecosystems articulating with each other, these include, corals, mangroves, algae, fisheries, invertebrates and microbiota of each one of these along with microbiota of the Red Sea waters and sediments. Studying the collective microbial communities of the Egyptian Red Sea coastal sediments have not been reported before. In regards to the severe pollution impacting the different Red Sea ecosystems, sediments samples have been collected from different impacted sites. The selected sites included 1- four ports for shipping aluminum, ilmenite and phosphate, 2-a site previously reported to have suffered extensive oil spills, 3-a reported tourism impacted site 4- two mangrove sites and 5-two lakes. Bacterial communities for each site have been studied through two different approaches, Culture-Dependent and Culture-Independent approaches. Pyrosequencing of V6-V4 hypervariable regions of 16S rDNA, isolated through the two approaches, has been used to assess the microbial community of each site. Physical parameters, Chemical analysis for 29 elements, selected semi-volatile oil contents, along with Carbon, Hydrogen, Nitrogen and Sulfur (CHNS) contents have been measured for each site. 131,402 and 136,314 significant reads have been generated through the Culture-Dependent and Independent approaches, respectively. Generally, Proteobacteria, Firmicutes, Actinobateria, Fusobacteria, Gemmatimonadetes and Bacteriodetes are the major bacterial groups detected through the two approaches. The Culture-Dependent datasets distinctive analysis revealed three main patterns (1) marine Vibrio spp.-suggesting a "marine Vibrio phenomenon"; (2) potential human pathogens; and (3) oil-degrading bacteria. While the Culture-Independent datasets analysis reported (1) an Egyptian Red Sea Coastal Microbiome, taxa detected in all the sites and (2) Hydrocarbon biodegrading bacteria predominance to the majority of the sites; particularly in two ports. On the other hand, the two lakes, through the two approaches, showed unique bacterial patterns, which generally grouped into anaerobic, halophilic and sulfur metabolizing bacteria. Individually, sites showed unique evolution of their microbial communities based on minor intrinsic and imposed variation per sites. Our results draw attention to the effects of different sources of pollution on the Red Sea and suggest the need for further analysis to overcome the hazardous effects observed at the impacted sites.